Strategies and Applications of Graphene and Its Derivatives-Based Electrochemical Sensors in Cancer Diagnosis - Li Fu; Yuhong Zheng; Xingxing Li; Xiaozhu Liu; Cheng-Te Lin; Hassan Karimi-Maleh (Molecules, 2023)
Graphene is an emerging nanomaterial increasingly being used in electrochemical biosensing applications owing to its high surface area, excellent conductivity, ease of functionalization, and superior electrocatalytic properties compared to other carbon-based electrodes and nanomaterials, enabling faster electron transfer kinetics and higher sensitivity. Graphene electrochemical biosensors may have the potential to enable the rapid, sensitive, and low-cost detection of cancer biomarkers. This paper reviews early-stage research and proof-of-concept studies on the development of graphene electrochemical biosensors for potential future cancer diagnostic applications. Various graphene synthesis methods are outlined along with common functionalization approaches using polymers, biomolecules, nanomaterials, and synthetic chemistry to facilitate the immobilization of recognition elements and improve performance. Major sensor configurations including graphene field-effect transistors, graphene modified electrodes and nanocomposites, and 3D graphene networks are highlighted along with their principles of operation, advantages, and biosensing capabilities. Strategies for the immobilization of biorecognition elements like antibodies, aptamers, peptides, and DNA/RNA probes onto graphene platforms to impart target specificity are summarized. The use of nanomaterial labels, hybrid nanocomposites with graphene, and chemical modification for signal enhancement are also discussed. Examples are provided to illustrate applications for the sensitive electrochemical detection of a broad range of cancer biomarkers including proteins, circulating tumor cells, DNA mutations, non-coding RNAs like miRNA, metabolites, and glycoproteins. Current challenges and future opportunities are elucidated to guide ongoing efforts towards transitioning graphene biosensors from promising research lab tools into mainstream clinical practice. Continued research addressing issues with reproducibility, stability, selectivity, integration, clinical validation, and regulatory approval could enable wider adoption. Overall, graphene electrochemical biosensors present powerful and versatile platforms for cancer diagnosis at the point of care.